2017
DOI: 10.1037/xhp0000398
|View full text |Cite
|
Sign up to set email alerts
|

Attention mediates the flexible allocation of visual working memory resources.

Abstract: Though it is clear that it is impossible to store an unlimited amount of information in visual working memory (VWM), the limiting mechanisms remain elusive. While several models of VWM limitations exist, these typically characterize changes in performance as a function of the number of to-be-remembered items. Here, we examine whether changes in spatial attention could better account for VWM performance, independent of load. Across 2 experiments, performance was better predicted by the prioritization of memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
139
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(171 citation statements)
references
References 39 publications
29
139
2
1
Order By: Relevance
“…Here we have focused on experiments in which each item in an array is equally likely to be tested and so has equal priority for representation. However, the view of WM as a limited resource has also been motivated by studies showing that prioritized items can be represented more precisely in WM, at the cost of decreased precision for other items [7,[19][20][21][22]. The population coding model has previously been shown to reproduce data from tasks that encourage unequal allocation of resources (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we have focused on experiments in which each item in an array is equally likely to be tested and so has equal priority for representation. However, the view of WM as a limited resource has also been motivated by studies showing that prioritized items can be represented more precisely in WM, at the cost of decreased precision for other items [7,[19][20][21][22]. The population coding model has previously been shown to reproduce data from tasks that encourage unequal allocation of resources (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…3). Importantly, discrete representations are compatible with an underlying continuous memory resource that can be distributed according to behavioral goals [25][26][27]: indeed in the stochastic model the integer number of samples available for each item at retrieval is unpredictable, and so cannot be the basis of prioritization. Instead, the resource distributed between items corresponds to the mean or expected total number of samples, which is constant and continuous-valued -in the neural model [2] this is equated with the instantaneous firing rate or membrane potential, while decoding is based on the expression of this rate in discrete spikes.…”
mentioning
confidence: 99%
“…Many influential attention papers suggest that the principal function of attention is to be a filter on sensory input, narrowing incoming stimuli down to a manageable stream of information that can be processed effectively with the brain's limited resources . The precise resource being competed for, however, has not been thoroughly characterized . Attention has also been proposed to be a mechanism that supports the flexible routing of information through the brain .…”
Section: The Diverse Functions Of Attentionmentioning
confidence: 99%
“…[39][40][41] The precise resource being competed for, however, has not been thoroughly characterized. 42 Attention has also been proposed to be a mechanism that supports the flexible routing of information through the brain. 43 Alongside its ability to select information for elaborated processing, attention is also thought to have the ability to suppress distracting or unneeded information.…”
Section: The Diverse Functions Of Attentionmentioning
confidence: 99%
“…In this way, the proportion of attentional resources allocated to any 1 given memory item can continuously vary anywhere between 0 and 100%. In these past 2 studies 18,19 , it was found that working memory performance (i.e., raw error = 1/precision) was 3 best predicted by the likelihood that an item would be probed on a given trial, independent of the 4 overall memory load. Importantly, this relationship between probe likelihood and memory 5 precision, which followed a power-law, could also account for changes in performance across 6 loads; for example, the change in precision from one to two items was consistent with each item 7 only receiving half as many attentional resources.…”
mentioning
confidence: 99%